Human Cardiac Pericytes Are Susceptible to SARS-CoV-2 Infection - Brumback, Brittany D.; Dmytrenko, Oleksandr; Robinson, Ashley N.; Bailey, Adam L.; Ma, Pan; Liu, Jing; Hicks, Stephanie C.; Ng, Sherwin; Li, Gang; Zhang, David M.; Lipovsky, Catherine E.; Lin, Chieh-Yu; et al. (JACC. Basic to translational science, 2023)
[Display omitted] •SARS-CoV-2 infects and replicates within cardiac pericytes in human organotypic cardiac slices.•SARS-CoV-2 infects human primary cardiac pericytes through an ACE2- and endosomal-dependent pathway.•Infection of human primary cardiac pericytes leads to up-regulation of inflammatory chemokine and cytokine expression, type I IFN signaling, mediators of vasoreactivity, and NF-κB–dependent cell death.•SARS-CoV-2 directly infects cardiac pericytes in patients with COVID-19 myocarditis. COVID-19 is associated with serious cardiovascular complications, with incompletely understood mechanism(s). Pericytes have key functions in supporting endothelial cells and maintaining vascular integrity. We demonstrate that human cardiac pericytes are permissive to SARS-CoV-2 infection in organotypic slice and primary cell cultures. Viral entry into pericytes is mediated by endosomal proteases, and infection leads to up-regulation of inflammatory markers, vasoactive mediators, and nuclear factor kappa-B–dependent cell death. Furthermore, we present evidence of cardiac pericyte infection in COVID-19 myocarditis patients. These data demonstrate that human cardiac pericytes are susceptible to SARS-CoV-2 infection and suggest a role for pericyte infection in COVID-19.